Palmitoylation in cardiometabolic diseases: From molecular mechanisms to clinical implications - Shenghui Feng; Yue Zhou; Linjuan Guo; Yan Liang; Wengen Zhu (Pharmacological Research)
Cardiometabolic diseases (CMDs), encompassing both cardiovascular diseases and metabolic syndromes, are among the leading causes of global morbidity and mortality. Protein S-palmitoylation, a reversible lipid-based post-translational modification, has emerged as a crucial regulator of cellular function and homeostasis. Palmitoylation is catalysed by palmitoyl transferases (PATs), also known as ZDHHC (zinc finger Asp-His-His-Cys) proteins, while a series of deacylases mediate the process of depalmitoylation. By modulating protein hydrophobicity, stability, subcellular localization, enzymatic activity, and membrane trafficking, palmitoylation exerts profound effects on cellular function. Physiologically, maintaining normal palmitoylation-depalmitoylation cycle are crucial in regulating the activity and membrane localization of ion channels involved in cardiomyocyte electrophysiology, modulating endothelial metabolism, cell-cell interactions, and repair following vascular injury, as well as influencing insulin signalling in cardiomyocyte metabolism. In the aspect of pathogenesis, palmitoylation influences the development of CMDs such as coronary artery disease (CAD), heart failure (HF), hypertension, type 2 diabetes (T2D), diabetic cardiomyopathy (DbCM), obesity, and non-alcoholic fatty liver disease (NAFLD). Dysregulation of the palmitoylation-depalmitoylation cycle contributes to these pathological processes, exacerbating disease progression. This review systematically explores the biological functions of palmitoylation in cardiometabolic physiology and diseases, discussing potential therapeutic targets within the palmitoylation pathway. By maintaining normal palmitoylation-depalmitoylation cycle and preventing its dysregulation, novel strategies for the prevention and treatment of CMDs may be developed.